Biochemical alterations in plasma total bile acid, creatinine, sodium, potassium, chloride, and bicarbonate in rabbits overdosed with ibuprofen and supplemented with guava leaf (Psidium guajava) extracts - Mathew Folaranmi Olaniyan; Precious Oluwamosope Okunola (BLDE University Journal of Health Sciences, 2019)
STUDY BACKGROUND: Ibuprofen is an analgesic and a nonsteroidal anti-inflammatory drug while Psidium guajava leaf has antioxidative, antimicrobial, anti-inflammatory, and analgesic activities. AIM AND OBJECTIVE: The aim of the study is to evaluate plasma total bile acids (TBAs), creatinine, and electrolytes in rabbits overdosed with ibuprofen and supplemented with guava leaf (P. guajava) extracts. JUSTIFICATION: There exists a little information on the change in the plasma levels of TBA and electrolytes in ibuprofen toxicity supplemented with guava leaf extract. MATERIALS AND METHODS: Fifteen rabbits (weight – 0.8–1.4 kg; age – 1.5 ± 0.4 years, n = 5/group) were grouped into control (a); rabbits administered 1600 mg/KgBW of ibuprofen (B1) before being fed with 400 mg/KgBW of guava leaf aqueous extract (B2) and rabbits administered 1600 mg/KgBW of ibuprofen administration (C1) before being fed with 400 mg/KgBW of guava leaf methanolic extract (C2). Plasma creatinine, sodium, potassium, chloride, and bicarbonate levels were determined using COBAS C111 chemistry autoanalyzer while TBA was determined by spectrophotometry. RESULTS: The results showed a significant increase in the plasma level of TBA, potassium, and creatinine in the rabbits following the administration of 1600 mg/KgBW of ibuprofen (P < 0.05) and a significant decrease in the plasma TBA, potassium, and creatinine in the same rabbits when they were given 400 mg/KgBW of guava leaf extract following ibuprofen overdose (P < 0.05). CONCLUSION: There was a significant increase in the plasma values of TBA, creatinine, and potassium following the administration of ibuprofen possibly due to ibuprofen toxicity which was significantly reduced upon the administration of 400 mg/KgBW of guava leaf extract.